A handbook of terrorism and insurgency in Southeast Asia - Tan, Andrew T. H. (Andrew Tian Huat) (Edward Elgar, 2009)
Seeks to explain the deep-seated complexities of terrorism and insurgency in Southeast Asia. This book argues that armed rebellion in Southeast Asia is a phenomenon that predates Al Qaeda and the global Jihadist movement and that much can be learned from the motivations behind it. It demonstrates the difficulty of rebellion in Southeast Asia.